Розробка комплексних техніко-технологічних заходів підвищення працездатності сільськогосподарських машин - Роговський, Іван Леонідович (НУБіП України, 2021)
Дисертація на здобуття наукового ступеня доктора наук зі спеціальності 05.05.11 «Машини і засоби механізації сільськогосподарського виробництва» (технічні науки). Національний університет біоресурсів і природокористування України, Київ, 2021. Дисертація присвячена підвищенню працездатності сільськогосподарських машин шляхом розробки системи, нормативів, технологій та технічних засобів їх технічного обслуговування і вивчення показників надійності цих машин в умовах експлуатації. В результаті досліджень здійснено аналіз сучасних методологічних основ і техніко-технологічних заходів підвищення працездатності сільськогосподарських машин. Здобувачем виконано аналітичне дослідження моделей комплексних техніко-технологічних заходів підвищення працездатності сільськогосподарських машин. Ним обґрунтовано загальні методичні підходи і розроблено методику експериментальних досліджень комплексних техніко-технологічних заходів підвищення працездатності сільськогосподарських машин. Також проведено експериментальні дослідження сезонних показників експлуатаційної довговічності, безвідмовності, ремонтопридатності і комплексного показника надійності сільськогосподарських машин. В дисертації проведено експериментальні дослідження оцінювання пристосованості до технічного обслуговування сільськогосподарських машин. Дисертант апробував виробничу ефективність комплексних техніко-технологічних заходів підвищення працездатності сільськогосподарських машин. Здобувачем здійснено техніко-економічний аналіз комплексних техніко-технологічних заходів підвищення працездатності сільськогосподарських машин
The dissertation on competition of a scientific degree of doctor of technical sciences, specialty 05.05.11 Machines and means of mechanization of agricultural production (technical sciences). National University of Life and Environmental Sciences of Ukraine, Kyiv, 2021. The dissertation is devoted to improving the performance of agricultural machines by developing a system, norms, technologies and technical means of their maintenance and studying indicators of reliability of these machines in operating conditions. As a result of research, an analysis of modern methodological foundations and technical and technological measures to increase the performance of agricultural machines is carried out. An analytical study of models of comprehensive technical and technological measures to increase the performance of agricultural machines is carried out. The general methodological approaches are substantiated and developed a method for experimental studies of complex technical and technological measures to increase the performance of agricultural machines. Experimental studies of seasonal indicators of operational durability, failure, reparability and complex indicator of reliability of agricultural machines were conducted. In the dissertation experimental studies of assessment of adaptability to the maintenance of agricultural machines were conducted. The dissertation tested the production efficiency of complex technical and technological measures to increase the performance of agricultural machines. The applicant has a technical and economic analysis of comprehensive technical and technological measures to increase the performance of agricultural machines. The results of researches of agricultural machines allow to state, the share of control and gas-filling works in maintenance comes about 30% of all labour intensity of maintenance. The total number of points of oiling 24–76, refuelling and drainage reaches 2–15 units, and varieties of oils and lubricants are used – 3–8. Low indicators of stability of fastening on machines is due to the lack of self-controlling threaded joints, low quality of mounting materials. Up to 36% of labour intensity comes to perform auxiliary work due to low availability to places in control and connecting control and regulators. The ergonomics of the machine is characterized by the convenience of performing operations in the process of its maintenance. So change the allows for lubricating operations to change productivity from 520 to 260 movements per hour. Violation of the rules for maintenance of a grain harvester and an evaluation of the events: incorrect regulation of the pressure of the start of fuel injection, low-quality screw – 0.463; gaps in the valve mechanism of the gas distributor outside the permissible values – 0.348; marginal contamination of air cleaning cassettes; violation of tightness of the inlet tract – 0.307; incorrect installation angle of fuel supply – 0.233. The introduction of comprehensive technical and technological measures to increase the performance of agricultural machines on the agricultural enterprise significantly improves the indicators for reducing the time by 15–18% compared to the operating system of agricultural machinery. It operating agricultural machines with a system of integrated technical and technological measures to increase the performance, the average work on refusal increased by 18.9%, while specific costs decreased by 26.8%, which is an appropriate value and is within the accuracy of simulation. However, this can be explained by the fact that the elements selected have a low probability of refusal, which for most elements is within 0.5–0.7. The influence of numerical characteristics of the time of technological operations to change the actual number of technical services is practically sufficiently small 0.5%. In the condition of stability in the accommodation of the agricultural machine in the process of their technical operation, the coefficient of time variation between technical services on a agricultural machine has a small value to 0.05...0.10, in connection with which there is a slight deviation of the actual number of technical services from the projected, as well as high to 0.85...0.95 probability of coinciding of predicted and actual terms up to 0.85. In the current normative documentation for ensuring the performance of agricultural machines, the following disadvantages are available: 48% reference to national and sectoral standards that have lost validity; 23% underestimated and 7% do not determine the quality indicators of the technological process of increasing the performance of agricultural machines; 11% do not indicate the operating conditions of agricultural machines; 18% contain underestimate performance indicators of reliability of agricultural machines. To date, the system of technical and technological measures to increase the performance of agricultural machines is normalized by six legislative and four normative documents and no state target economic program
Keywords: сільськогосподарська машина; працездатність; параметр; технічне обслуговування; технічний стан; система; комплексний захід; agricultural machine; performance; parameter; maintenance